ANALISIS PENGARUH BELANJA MODAL, INFRASTRUKTUR JALAN, INDEKS PEMBANGUNAN MANUSIA DAN ANGKATAN KERJA TERHADAP PRODUK DOMESTIK REGIONAL BRUTO DI PROVINSI SUMATERA UTARA - Pratama, Ramadhan Devan; Hasyim, Sirojuzilam; Pratomo, Wahyu Ario; Lubis, Irsyad (Jurnal Kajian Ekonomi dan Kebijakan Publik (JEpa), 2022)
This study aims to determine the effect of Capital Expenditure, Road Infrastructure, Human Development Index and Labor Force on Gross Regional Domestic Products in the province of North Sumatra. The type of data used is the type of quantitative data that is data that is numerically processed using statistical methods. The data used in this study are secondary data witha panel data types (combined time series and cross section) from 2012-2020 in 33 districts/cities in North Sumatra. The variables used are GRDP (Y), Capital Expenditure (X1), Road Infrastructure (X2), Human Development Index (X3) and Labor Force (X4). In analyzing the data used panel data regression model using Eviews 9. From the results of this study indicate that Capital Expenditure has a positive and significant effect on GRDP, Road Infrastructure has a positive and no significant effect on GRDP, Human Development index has a positive and significant effect on GRDP and Labor Force has a positive and significant effect on GRDP.